The Concept of Ahl Al-Sunnah Wa Al-Jamаah in Increasing Religious Harmony from KH Hasyim Asy'ari Perspective. - Sulaiman; Sutrisno, Andri (Penerbit Hellow Pustaka, 2025)
This study examines the role of the Ahl Al-Sunnah Wa Al-Jama’ah (ASWAJA) concept in interreligious harmony based on the thoughts of KH. Hasyim Asy’ari, the founder of Nahdlatul Ulama (NU). Employing a qualitative approach with library research methods, the study analyzes KH. Hasyim Asy’ari’s seminal work (Risalah Ahl Al-Sunnah Wa Al-Jama’ah) and related literature. The findings reveal that ASWAJA operates as a theological-social framework through three mechanisms: (1) the authority structure of ulama (scholars) as guardians of moderation, (2) core values (tawassuth [moderation], tasamuh [tolerance], tawazun [balance]), and (3) Islamic boarding schools (pesantren) as laboratories of harmony. ASWAJA’s values such as social justice (al-‘adalah al-ijtima’iyyah), human brotherhood (al-ukhuwwah al-insaniyyah), and deliberation (al-syura) provide practical foundations for interfaith relations. The study concludes that KH. Hasyim Asy’ari’s thought offers a model of harmony rooted in Indonesian Islamic tradition, which remains relevant to contemporary multireligious societies.